Identification of Resistance to Bacterial Blight in Introgression Lines of Yuanjiang Common Wild Rice and Analysis of Its Japonica Indica Properties - Wang KAN; Hesheng YANG; Huanzhi MENG; Jiyun ZHOU; Zaiquan CHENG; Yun ZHANG; Suqin XIAO; Li LIU; Bo WANG; Fuyou YIN; Qiaofang ZHONG; Jinlu LI; et al. (Guangdong nongye kexue)
【Objective】Yuanjiang common wild rice has strong resistance to bacterial blight, however, its differentiation between japonica and indica is not obvious. Yuanjiang common wild rice introgression lines were used to analyze the resistance to bacterial blight and the differentiation of japonica and indica, and to further explore the correlation between these two traits, which could provide a basis for efficient mining and utilization of excellent disease-resistance gene resources from Yuanjiang common wild rice.【Method】A total of 280 Yuanjiang common wild rice introgression lines were used as research subjects to analyze the japonica and indica properties by molecular marker technology, and the resistance to bacterial blight was identified by artificial inoculation experiments. The correlation between these two traits was discussed by statistical analysis.【Result】The results of japonica and indica property analysis showed that among 280 introgression lines, indica rice types were dominant, with a total of 218 samples, while japonica rice types had 61 samples, and the japonica and indica properties of another one could not clearly be distinguished. The results of artificial inoculation experiments showed that the resistance intensity of these introgression lines to Chinese standard bacterial blight (C4-C9) ranked as: C4 > C7 > C6 > C5 > C9 > C8. Different introgression lines showed broad-spectrum resistance to six strains. Further correlation analysis revealed that indica samples also showed broad-spectrum resistance, and in both resistant and susceptible samples, the proportion of indica samples and the average lesion length were significantly different from those of japonica samples. The indica gene frequency was negatively correlated with the lesion length caused by strain infection, while the japonica gene frequency was positively correlated with it.【Conclusion】The introgression lines of Yuanjiang common wild rice had obvious japonica-indica differentiation, and showed diversified resistance to Chinese standard bacterial blight (C4-C9), among which the indica rice types showed higher resistance and wider resistance spectrum.